Causal Relationships Among Factors Affecting the Buildability in Executing Construction Projects in Vietnam - Pham, Hai; Kim, Soo-Yong; Luu, Truong-Van; Lam, Phu-Son (Proceedings of Engineering and Technology Innovation, 2017)
This paper aims to identify causal relationships among factors affecting the buildability in executing construction projects in Vietnam. First, through a comprehensive literature review, the study identified a full set of attributes that affect the buildability of construction projects. Subsequently, through discussions and interviews with experts, the study determined main attributes affecting the buildability in the context of the construction industry in Vietnam. After that, a survey questionnaire was developed which was based on identified attributes. The data after collected, was analysed by Structural Equation Model (SEM) and the expected result from the SEM model is a structural model. This structural model includes four factors, namely: Design applies advanced machinery, materials and construction methods; Design uses available resources at local for saving costs; Design applies safe construction methods; and Design uses prefabricated and typical components. The key finding of the study is to provide insights into causal relationships among factors affecting the buildability in executing construction projects in Vietnam.